Analysis of Digital Literacy Through the Quizizz Application in Civic Education Course - Ni Putu Candra Prastya Dewi; Gusti Agung Ayu Wulandari; Made Sri Astika Dewi; Ni Putu Juni Artini; I Gusti Ayu Putu Novita Sari Paragae; Putu Gede Asnawa Dikta (Journal of Innovation in Educational and Cultural Research, 2025)
In the 21st century, students have not utilized technology well. They are used to using cell phones primarily for entertainment, such as playing online games. They have not fully utilized technology for education, which can develop their digital literacy. Thus, they lack digital literacy. This study aimed to analyze digital literacy using an educational application named “Quizziz” in the Civic Education course. The respondents were 106 1st-semester students taking the Civic Education course. The data were obtained using a questionnaire containing 20 written statements and responses via Google Forms. The average and the AAL (Average Achievement Level) were calculated and categorized according to the category table for data analysis. This study revealed that the total average of 4 digital literacy competencies was 4.37 with an AAL of 87.4%, which was categorized as good. This shows that using Quizizz in the Civic Education course can positively affect the digital literacy of the Elementary School Teacher Education Study Program of STAHN Mpu Kuturan. This research contributes knowledge about using technology-based learning to improve students' digital literacy.